Financial disclosure and the Board: A case for non-independent directors - Yuri Biondi; Pierpaolo Giannoccolo; Antoine Reberioux (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
In listed companies, the Board of directors has ultimate responsibility for information disclosure. The conventional wisdom is that director independence is an essential factor in improving the quality of that disclosure. In a sense, this approach subordinates expertise to independence. We argue that effective certification may require firm-specific expertise, in particular for intangible-intensive business models. However, this latter form of expertise is negatively related to independence as it is commonly measured and evaluated. Accordingly, there exists an optimal share of independent directors for each company, related to the level of intangible resources.
Keywords: G30; M21; D80; M41; 330